01 Tristetraprolin Post-Transcriptionally Regulates Tissue Factor Expression in Primary Human and Murine Macrophages. (20th November 2012) - Iqbal, MB; Dean, JE; Burke, N; Clark, A; Johns, M; Haskard, DO
Abstract : Background: Although monocyte-derived tissue factor (TF) plays critical roles in atherothrombosis, little is known about its post-transcriptional regulation. Tristetraprolin (TTP) binds the 3′UTR of target mRNAs and promotes their degradation, with its function being negatively regulated by p38 MAPK. Whether TTP post-transcriptionally regulates TF is unknown. Methods: We used human monocytes and bone marrow derived macrophages from TTP+/+ and TTP-/- mice. Procoagulant activity was determined using a clot turbimetric assay. mRNA decay was determined following transcriptional arrest using actinomycin D. TTP knockdown was achieved using siRNA transfection. RNA and protein interaction was determined using ribonucleoprotein (RNP) immunoprecipitation and RNA biotin pulldown assays. Results: p38 inhibition with SB203580 and SB202190 (1µMM) reduced procoagulant activity, TF mRNA and protein expression in human macrophages (p<0.05). p38 inhibition reduced TF mRNA stability in both human and murine macrophages (p<0.05). TTP knockdown increased TF expression in human macrophages (p<0.05). Both TF mRNA and protein expression were significantly increased in TTP-/- versus TTP-/- macrophages (p<0.05). Moreover TF mRNA decay was reduced in TTP-/- macrophages and p38 inhibition had no effect on this (p<0.01). RNP immunoprecipitation demonstrated TTP and TF mRNA interaction. Furthermore, a more specific interaction with TTP and TF 3′UTR was confirmed using RNA biotin pulldown techniques. Conclusions: These data provide evidence, for the first time, that p38 and TTP post-transcriptionally regulate TF expression in macrophages. A better understanding of the post-transcriptional regulation of TF expression will provide novel insights into the interface between inflammation and thrombosis in vascular biology, and holds therapeutic potential.